Euro area sovereign debt: Restructuring options - Theresa Arnold; Mitu Gulati; Ugo Panizza (Graduate Institute of International and Development Studies, 2019)
Countries with large debts stocks are vulnerable to the vagaries of the markets. Confidence crises can arise out of nowhere, constricting access to the markets. Hence, the question arises as to whether these countries should put in place mechanisms that will help them better prepare for the possibility of crisis. In effect, the choice is whether to buy insurance. The cost of buying such insurance is that the possibility that markets will see the sovereign's proactive steps to protect against a crisis not as an indication of prudent governance but rather as an indicator that a crisis is imminent. In this article, we use the case of a hypothetical euro area country (Italy) with a large debt stock and a known vulnerability to confidence crises to set forth its options, as of 2019, to anticipate a possible future debt restructuring. It can: do nothing, do a little; and do something substantial.
Keywords: F34; F54; G15; H12; H63; K22; 330; Sovereign debt; Italy; euro area; restructuring; local law advantage